A comparative ecotoxicological study of heavy metal concentrations in mussels collected in 2004 from the western and eastern coastal waters in the Straits of Johore - Kong Yap, Chee; Franklin Berandah, Edward; Saupi Ismail, Mohamad; Okamura, Hideo; Horie, Yoshifumi; Chuan Ong, Meng; Dwi Setyawan, Ahmad; Wah Yap, Chee; Othman, Azahari; Seng Leow, Chee (MedCrave Group, LLC, 2023)
The concentrations of Cu, Cd, Zn, Pb, Ni and Fe in the different soft tissues of Perna viridis from the west and east coast of The Straits of Johore (SOJ) were determined. Crystalline style (CS) recorded higher accumulation of Cu (west: 58.2 mg/kg dry weight; east: 56.0 mg/ kg dry weight), Cd (west: 9.45 mg/kg dry weight; east: 3.93 mg/kg dry weight), Pb (west: 49.5 mg/kg dry weight; east: 7.07 mg/kg dry weight) and Ni (west: 40.0 mg/kg dry weight; east: 20.2 mg/kg dry weight) than those other soft tissues. Byssus meanwhile recorded high levels of Zn (west: 173 mg/kg dry weight; east: 193 mg/kg dry weight) and Fe (west: 3213 mg/kg dry weight; east: 1221 mg/kg dry weight). By comparing the accumulation of heavy metal concentrations in all the eight tissues, CS and byssus recorded the highest accumulation of heavy metals among all tissues, followed by other tissues namely foot, gill, gonad, mantel, muscle and remainder, which recorded relatively low level on heavy metal concentrations. Generally, the soft tissues recorded higher heavy metal concentrations on the east coast than on the west coast of the SOJ. This indicated a high bioavailability and contamination of the potentially toxic heavy metals on the east coast which was due to various human activities.